Faktor Motivasi dengan Implementasi Sistem Jenjang Karir Perawat Pelaksana - Fauziah Fauziah; Jenny Marlindawani Purba; Roxsana Devi Tumanggor (Journal of Telenursing (JOTING), 2021)
This study aims to determine the relationship between the motivation of implementing nurses with the implementation of the career path system in the RSU. The research design used is a descriptive correlation with a cross-sectional design. Data were analyzed by a chi-square statistical test. The results showed that the p-value in the analysis of the relationship between motivation and the implementation of the career path system for nurses was 0.022. In conclusion, there is a relationship between motivation and implementing the career path system for implementing nurses at RSU. Keywords: Career Path, Motivation, Nurse Practitioner